(3eNJGQ OjhGf GHf bdGbS GdEScfOQjs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg eSOO SgGe GdacQ dCZQGVgG hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg ZjhK GdeOM hQjGVgG s
(3BNQgG (B:s
(3CQSdJ dj SWQjf bO LeYG oMebG Ydjc jMQe GdHbjG aYOeJgG ef QbYI hQOJ hdh CfgG dj QbYI aj GdOfjG Je GdeNJGQ ef OjhGf s
(3GHf bdGbS GdEScfOQj gh CHhGdaJhM fUQ Hf YHOGddg Hf YHOGdbhj GddNej GdCRgQjs
(3GdeJhai (B567 (3g`````s
(3eQJH Ydi MQha GdeYLe hjVe fMh (B1850 (3HjJkGs
(3hHgG fXGe GdJYbjHIs
(3UaMGJgG eLOhdI HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs